Incidence of cytomegalovirus infection in seropositive kidney transplant recipients treated with everolimus: A randomized, open‐label, multicenter phase 4 trial. Issue 5 (19th January 2022) - Kaminski, Hannah; Kamar, Nassim; Thaunat, Olivier; Bouvier, Nicolas; Caillard, Sophie; Garrigue, Isabelle; Anglicheau, Dany; Rérolle, Jean‐Philippe; Le Meur, Yannick; Durrbach, Antoine; Bachelet, Thomas; Savel, Hélène; et al.
Abstract : Cytomegalovirus (CMV) persists as the most frequent opportunistic infection among solid organ transplant recipients. This multicenter trial aimed to test whether treatment with everolimus (EVR) could decrease the incidence of CMV DNAemia and disease. We randomized 186 CMV seropositive kidney transplant recipients in a 1:1 ratio to receive EVR or mycophenolic acid (MPA) in association with basiliximab, cyclosporin, and steroids and 87 in each group were analyzed. No universal prophylaxis was administered to either group. The composite primary endpoint was the presence of CMV DNAemia, CMV treatment, graft loss, death, and discontinuation of the study at 6 months posttransplant. In the modified intent‐to‐treat analysis, 42 (48.3%) and 70 (80.5%) patients in the EVR and MPA groups reached the primary endpoint (OR = 0.21, 95% CI: 0.11–0.43, p < .0001). Fewer patients of the EVR group received treatment for CMV (21.8% vs. 47.1%, p = .0007). EVR was discontinued in 31 (35.6%) patients. Among the 56 patients with ongoing EVR treatment, only 7.4% received treatment for CMV. In conclusion, EVR prevents CMV DNAemia requiring treatment in seropositive recipients as long as it is tolerated and maintained. Abstract : This French multicentre trial demonstrates that treatment with everolimus reduces the incidence of CMV DNAemia and CMV DNAemia requiring antiviral treatment.